A study of some aspects of the formation and performance of atomic vapour in a graphite atom reservoir for atomic fluorescence spectrometry - Martin, T. L.(Thomas Linsent) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1973.